Analisis Tingkat Ketergunaan Aplikasi Perpustakaan Universitas Quality dalam Mendukung Tujuan Pembangunan Berkelanjutan (SDGs) - Wijaya, Surya Hadi; Sayekti, Retno (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The importance of library digitization in the context of the times is not only related to the provision of satisfactory services, library digitization is a response to technological developments, but also an effort in achieving SDGs. This research aims to analyze the role played by Quality University Library in facilitating access to information. The System Usability Scale (SUS) method was adopted for this research. Data collection was done through the Google Forms platform by conducting a survey. The results of the SUS calculation show that the average value of the usability of the Quality University library application is 63, which is in the sufficient category. Further analysis shows that there are still aspects that need to be improved, namely promotion. The conclusion of this study is that the library application still needs to increase its promotion to students so that not only final semester students are actively using the application.